2021
DOI: 10.1101/2021.06.23.449580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Features Underlying Shp1/Shp2 Discrimination by Immune Checkpoint Receptors

Abstract: Numerous inhibitory immunoreceptors operate by recruiting phosphatase effectors Shp1 and Shp2 through conserved motifs ITIM and ITSM. Despite the similarity, these receptors exhibit distinct effector binding specificities, as exemplified by PD-1 and BTLA, which preferentially recruit Shp2 and Shp1 respectively. The molecular basis of Shp1/Shp2 discrimination is unclear. Here, we provide evidence that optimal PD-1 and BTLA binding to both Shp1 and Shp2 occurs via a bivalent, parallel mode that involves both SH2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Fiji was used to quantify the fluorescent intensities of TIGIT or PD-1 in CD226 microclusters (Schindelin et al, 2012). Mask images identifying the area of CD226 microclusters were generated by applying the ''subtract background'' command to CD226 (mGFP) images using the default setting (Xu et al, 2021). The fluorescent signals of CD226 (mGFP), TIGIT (mCherry), or PD-1 (mApple) in the masked overlaid images were measured, and used to calculate the CD226 FI/TIGIT FI or CD226 FI/PD-1 FI ratio for each cell.…”
Section: Jurkat:slb Imaging Assaymentioning
confidence: 99%
“…Fiji was used to quantify the fluorescent intensities of TIGIT or PD-1 in CD226 microclusters (Schindelin et al, 2012). Mask images identifying the area of CD226 microclusters were generated by applying the ''subtract background'' command to CD226 (mGFP) images using the default setting (Xu et al, 2021). The fluorescent signals of CD226 (mGFP), TIGIT (mCherry), or PD-1 (mApple) in the masked overlaid images were measured, and used to calculate the CD226 FI/TIGIT FI or CD226 FI/PD-1 FI ratio for each cell.…”
Section: Jurkat:slb Imaging Assaymentioning
confidence: 99%
“…In addition, SHP1 and SHP2 both contain two contiguous SH2 domains. 52,53 Using sequence alignment and phylogenetic tree methods, Andersen et al compared and analyzed the evolution relationships among vertebrate PTKs, and confirmed that the sequence of SHP2 is closest to the homologous protein SHP1 with a similarity of 60%. 54 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%